Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on the macroprudential policy framework. The authorities have strengthened the institutional arrangement for macroprudential policy by enhancing the Netherlands Bank's legal mandate and establishing the Financial Stability Committee, but there is room for improvement. The authorities' analysis of systemic vulnerabilities is sophisticated and timely. The authorities have been using the range of macroprudential instruments at their disposal, but further tightening will be necessary to contain a potential buildup of systemic risk in the financial system.